Identification of Train Braking Systems using Failure Mode And Effect Analysis Method at UPT Balai Yasa Surabaya Gubeng - Shofi Fitrotis Salimah; Sugeng Purwoko; Mu’alim; Ahmad Muqorrobin Ardiansyah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Quality control of the train braking system is a critical aspect of ensuring the safety of many train passengers. This study aims to analyze the factors that will influence the failure of the train braking system, especially the problematic braking components, to improve the quality standards of the train braking system. The Failure Mode and Effect Analysis (FMEA) method is proposed to identify potential causes of failure—train braking systems. The main components of train braking, critical systems, failure modes, and causes of failure are analyzed, and preventive measures are suggested to reduce the impact of the failure. The results showed that the highest cause of failure of 49% was the failure of the braking system components in the control valve with an RPN value of 720, which could cause the brake block to bind so that leaks could occur, and the brake system would not work.